2020
DOI: 10.1101/2020.09.06.285387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TWIST1 and chromatin regulatory proteins interact to guide neural crest cell differentiation

Abstract: Protein interaction is critical molecular regulatory activity underlining cellular functions and precise cell fate choices. Using TWIST1 BioID-proximity-labelling and network propagation analyses, we discovered and characterized a TWIST-chromatin regulatory module (TWIST1-CRM) in the neural crest cell (NCC). Combinatorial perturbation of core members of TWIST1-CRM: TWIST1, CHD7, CHD8, and WHSC1 in cell models and mouse embryos revealed that loss of the function of the regulatory module resulted in abnormal spe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 99 publications
2
2
0
Order By: Relevance
“…Early intervention of chd8 may be important for the newly delaminated vagal NCC progenitors to proceed to migratory stages. This possibility is in line with recent transcriptomic work on cranial NCCs in mice showing that the complex Chd8/Twist1 controls delaminatory and early migratory markers 46 . Contrary to Hirschsprung’s disease (HSCR; MIM#142623), a congenital condition associated with a failure of vagal NCCs to colonize the intestine 47,48 , we found that chd8 loss do not prevent the completion of the rostro-caudal colonization of the gastrointestinal tract by the vagal NCCs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Early intervention of chd8 may be important for the newly delaminated vagal NCC progenitors to proceed to migratory stages. This possibility is in line with recent transcriptomic work on cranial NCCs in mice showing that the complex Chd8/Twist1 controls delaminatory and early migratory markers 46 . Contrary to Hirschsprung’s disease (HSCR; MIM#142623), a congenital condition associated with a failure of vagal NCCs to colonize the intestine 47,48 , we found that chd8 loss do not prevent the completion of the rostro-caudal colonization of the gastrointestinal tract by the vagal NCCs.…”
Section: Discussionsupporting
confidence: 82%
“…NCC differentiation is governed by precise sequence of fate decisions at the right time and place 49 . We and others have shown that chd8 regulates gene expression in pathways involved in neurodevelopment, supporting a role for chromatin remodelers in neuronal differentiation 29,46,50,51 . However, chd8 function in enteric neurons has never been reported.…”
Section: Discussionsupporting
confidence: 65%
“…The diverse roles of CHD7 in the development of multiple tissues make for a challenge in determining the precise cellular and molecular pathways leading to each of the many CHARGE phenotypes. In the nervous system alone, CHD7 promotes neuronal differentiation (Feng et al, 2013; Feng et al, 2017; He et al, 2016; Jones et al, 2015), is required for proper neurite development (Yao et al, 2020), regulates cerebellar organization through RELN (Whittaker et al, 2017a), promotes GABAergic neuron development through paqr3 (Jamadagni et al, 2021) and is required for neural crest cell differentiation and migration (Fan et al, 2021; Okuno et al, 2017), thereby contributing to multiple disease manifestations such as cranial nerve, cardiac, and craniofacial defects (Wysocka et al, 2010). Our Exon 9 mutants display both morphological defects in the ear and a deficit in auditory LLC responses (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is more properly understood as referring to a family of neurocristopathies, the full identity of which will be revealed by future work. Even work focusing on the effect of a single hub gene (e.g BAZ1B 43 , or SOX9 56 , 57 , or Twist1 58 ) reveals that the relevant phenotype cannot be understood in the absence of downstream targets, each one of which is susceptible to modification 59 . As previously shown, the architecture of the neural crest is remarkably modular 60,61 (see 62 specifically for cranial neural crest), with several developmental decision points corresponding to distinct fate programs, affording a lot of variation 63 .…”
Section: What the Hypothesis Is (Not)mentioning
confidence: 99%